Penanaman Nilai Karakter Jujur Anak Melalui Kegiatan Bermain Peran Di Kelompok B PAUD Nusa Indah - Hesti; Niasari, Tanjung; Fitrawati (Student Journal of Early Childhood Education, 2024)
The aim of this research is to determine the value of children's honest character through role-playing activities in group B PAUD Nusa Indah. This research was conducted on all children in group B PAUD Nusa Indah. This type of research is This research is in accordance with descriptive qualitative methods. The data collected is in the form of words, images, and not numbers. This is caused by the application of qualitative methods. Based on the results of research and discussions conducted by researchers regarding instilling the value of honest character in children through role-playing activities, this activity has proven to be effective in changing children's behavior and thoughts regarding honesty. Instilling the value of honest character in children can have a positive impact on the child himself, and the people around him, including friends, teachers and parents at home. Through this role playing activity, children are taught to act as honest people, what the impact would be if they were not honest in everyday life.